Long COVID a perpetual threat even after COVID era? A case presentation - Hussain, Asraf; Ansari, Parwez Alam; Gupta, Ajay Kumar; Kushwaha, Omprakash; Shah, Rupesh; Yadav, Surendra; Kaushik, Pratibha (Nepalese Respiratory Journal, 2022)
Coronavirus disease 2019 (COVID-19) is a highly infectious disease. The acute phase of the disease has been focused upon and less importance is given to the long-term sequelae. A new term ‘long COVID’ is used to describe a diverse set of symptoms that persists for more than 12 weeks after a diagnosed COVID-19 infection with no alternative diagnosis. Predominant symptoms include persistent breathlessness, fatigue, cough, chest pain, palpitations, neurological and cognitive deficits, rashes, and gastrointestinal dysfunction. Risk factors for the development of long COVID are female gender, increased age, and increased BMI. Lung fibrosis is an important ailment in COVID survivors. Long COVID needs urgent attention for better understanding and specialized action plans to improve the quality of life in these patients and decrease their financial burden. Studies are warranted to investigate the early installation of antifibrotic agents in high-risk patients. Till we find better measures to counter long COVID, preventive measures and vaccination are the best available options. We are presenting here a case of long COVID who was admitted on multiple occasions for exacerbation of symptoms. He is now being managed on an outpatient basis.